Mossbauer Spectroscopy Study of Fe75.3Ni0.8Cr0.9Si8.7B14.3 Ferromagnetic Alloy after Thermal Annealing, Laser and Electron Beam Irradiation - Sorescu, Monica; Corcovilos, Theodore A; Higinbotham, Douglas; Stutzman, Marcy (European Journal of Applied Sciences, 2025)
This paper presents a Mӧssbauer spectroscopy study of the behavior of Fe75.3Ni0.8Cr0.9Si8.7B14.3 ferromagnetic alloy after thermal annealing, cw laser and high-energy electron beam irradiation. Thermal annealing at 450 oC caused structural relaxation of the alloy system, supported by an increase in the average magnetic hyperfine field and width of the field distribution, accompanied by a significant out-of-plane reorientation of the magnetic moment directions. Thermal annealing at temperatures of 550-750 oC determined crystallization of the bulk of the specimens and alpha-(FeNiCr), (FeNiCr)3(BSi) and (FeNiCr)2(BSi) crystalline phases were identified. At the highest treatment temperature, (FeNiCr)3(BSi) partially decomposed into alpha-(FeNiCr) and (FeNiCr)2(BSi). Cw laser irradiation essentially preserved the preferred in-plane orientation of the magnetic moment directions, with a slight tendency of an out-of-plane reorientation. Irradiation of the Fe75.3Ni0.8Cr0.9Si8.7B14.3 alloy system with 11 GeV electrons maintained the in-plane direction of bulk magnetization in the beam dump sample and caused an even more pronounced in-plane direction of the magnetic moments in the target platform sample. This is due to the low value of the magnetostriction constant of the Fe75.3Ni0.8Cr0.9Si8.7B14.3 system. Both laser and electron beam irradiation were demonstrated to keep the amorphous phase of the Fe75.3Ni0.8Cr0.9Si8.7B14.3 alloy, making it a strong candidate for radiation-resistant materials.